2016
DOI: 10.21474/ijar01/1161
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation Coefficient of Reactive Powder Concrete Using Different Energies.

Abstract: Linear and mass attenuation coefficient of reactive powder concrete (RPC) sample ( of compressive strength equal to 70 Mpa) using beta particles and gamma ray with different energies have been calculated as a function of the absorber thickness and energy. The attenuation coefficient were obtained using NaI(Tl) energy selective scintillation counter with 90 Sr/ 90 Y beta source having an energy rang from (0.546-2.274) MeV and gamma ray energies (0.569, 0.662, 1.063, 1.17 and 1.33) MeV . The attenuation coeffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Hence, it is so difficult to observe a complete descending stage. To solve this problem, steel fibers are usually added to improve ductility [6]. Many studies collectively demonstrated that adding steel fibers to RPC can significantly improve its mechanical properties, including compressive strength, flexural strength, toughness, and crack resistance; moreover, highlighting the positive influence of steel fibers on enhancing the performance and durability of RPC [2,5,[7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is so difficult to observe a complete descending stage. To solve this problem, steel fibers are usually added to improve ductility [6]. Many studies collectively demonstrated that adding steel fibers to RPC can significantly improve its mechanical properties, including compressive strength, flexural strength, toughness, and crack resistance; moreover, highlighting the positive influence of steel fibers on enhancing the performance and durability of RPC [2,5,[7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The concrete industry is aware of these materials' ability to enhance certain of the characteristics of regular concrete [17]. By testing linear and mass attenuation coefficients using several radiation sources with varying energies, Wasan et al [18] investigate the potential of employing reactive powder concrete as a shielding material. Reactive powder concrete was shown to be capable of absorbing beta particles and gamma rays without significantly reducing the specimen's compressive strength.…”
Section: Introductionmentioning
confidence: 99%
“…This, mainly, produced a very dense and low porosity material compared with other types of traditional concrete. Therefore; it can be considered as a good and economic choice for isolation and containment of nuclear waves [2,3]. Several studies were published regarding the effect of partial replacements of different materials instead of cement or sand [4, 5 and 6].…”
Section: Introductionmentioning
confidence: 99%